Baroreflex Activation Therapy for the Treatment of Drug-Resistant Hypertension: New Developments - Teba Alnima; Peter W. de Leeuw; Abraham A. Kroon (Cardiology Research and Practice)
In the past few years, novel accomplishments have been obtained in carotid baroreflex activation therapy (BAT) for the treatment of resistant hypertension. In addition, this field is still evolving with promising results in the reduction of blood pressure and heart rate. This overview addresses the latest developments in BAT for the treatment of drug-resistant hypertension. Although not totally understood considering the working mechanisms of BAT, it appeared to be possible to achieve at least as much efficacy of single-sided as bilateral stimulation. Therefore unlike the first-generation Rheos system, the second-generation Barostim neo operates by unilateral baroreflex activation, using a completely different carotid electrode. Also significant improvements in several cardiac parameters have been shown by BAT in hypertensive patients, which set the basis for further research to evaluate BAT as a therapy for systolic heart failure. Yet important uncertainties need to be clarified to guarantee beneficial effects; hence not all participants seem to respond to BAT.